2020
DOI: 10.24050/reia.v17i34.1408
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Active Edible Coatings Based on Yam Starch and Cassava Starch

Abstract: Aim. To compare the properties of active edible materials to active edible based on yam and cassava starch with the incorporation of essential oil of oregano (Origanum vulgare) (OEO) for application in grape coating. Materials and methods. The film-forming dispersions were obtained and the contact angle on different kinds of fruits and vegetables and the stability of the dispersions were determined. Subsequently, the films were obtained by casting, their physicochemical properties were evaluated, such as antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This antioxidant function is evaluated in consideration of the concentration of the antioxidant and the effect of the radical cation consumption limiting the reaction period. The results of this study showed that parsnip had excellent ABTS radical scavenging activity (Table 3), and compared with yam (17.12 mg g −1 ), parsnip's ABTS radical scavenging activity (55.50 mg TE g −1 ) was approximately two times higher (Ortega‐Toro et al ., 2020). This result is also well related to high concentrations of phenols, i.e .…”
Section: Resultsmentioning
confidence: 99%
“…This antioxidant function is evaluated in consideration of the concentration of the antioxidant and the effect of the radical cation consumption limiting the reaction period. The results of this study showed that parsnip had excellent ABTS radical scavenging activity (Table 3), and compared with yam (17.12 mg g −1 ), parsnip's ABTS radical scavenging activity (55.50 mg TE g −1 ) was approximately two times higher (Ortega‐Toro et al ., 2020). This result is also well related to high concentrations of phenols, i.e .…”
Section: Resultsmentioning
confidence: 99%